Reasons from within desires and values - Goldman, Alan H., 1945- (Oxford : Oxford University Press, 2009)
'Reasons from Within' defends the view that all our reasons for acting derive from our desires, and ultimately from our deepest concerns. There are no objective values in the world that could require our concerns to be other than they are. It will be of interest to anyone interested in the nature of values and reasons.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Values; Desire